2022
DOI: 10.3390/drones6050104
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Colony Social Learning Approach for the Self-Organization of a Swarm of UAVs

Abstract: This research offers an improved method for the self-organization of a swarm of UAVs based on a social learning approach. To start, we use three different colonies and three best members i.e., unmanned aerial vehicles (UAVs) randomly placed in the colonies. This study uses max-min ant colony optimization (MMACO) in conjunction with social learning mechanism to plan the optimized path for an individual colony. Hereinafter, the multi-agent system (MAS) chooses the most optimal UAV as the leader of each colony an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…They are also divided into two scenarios in terms of operation manner in the environment. In the first scenario, drones operate individually, while in the second scenario they fly in combination with others, which are normally known as a swarm of UAVs [32][33][34][35].…”
Section: State Of the Art Workmentioning
confidence: 99%
“…They are also divided into two scenarios in terms of operation manner in the environment. In the first scenario, drones operate individually, while in the second scenario they fly in combination with others, which are normally known as a swarm of UAVs [32][33][34][35].…”
Section: State Of the Art Workmentioning
confidence: 99%
“…However, the height of cliffs exceeds 100 m and the UAV must fly in the plane above the cliff, resulting in the unavailability of considerable information about the cliff, especially its bottom. Many studies have shown that in complex cliff conditions, the use of orthorectified and oblique images can reduce 3D modeling errors and optimize the survey route (Ali et al, 2019;Shafiq et al, 2022). The reason is that the more complex the angle of capture, the better the reproduction (Nesbit and Hugenholtz, 2019;Kozmus Trajkovski et al, 2020).…”
Section: Data Acquisition and Processingmentioning
confidence: 99%
“…Consequently, labor costs remain high and collecting relevant data remains time-consuming and labor-intensive. To meet the challenge of high-quality modeling (Burdziakowski, 2018), many state of the art in fields (Ali et al, 2019;Shafiq et al, 2022) use many technologies such as UAV and artificial intelligence for three-dimensional reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of swarm intelligence are regarding the environment, interactions, and activities of the individuals in a swarm. No direct communication takes among the individuals in a swarm [25]. They interact with each other through environmental alterations.…”
Section: Mechanism Of Simentioning
confidence: 99%